First molecular evidence of hybridization in endosymbiotic ciliates (Protista, Ciliophora) - Obert, Tomáš; Zhang, Tengyue; Rurik, Ivan; Vďačný, Peter (Frontiers in Microbiology, 2022)
Hybridization is an important evolutionary process that can fuel diversification via formation of hybrid species or can lead to fusion of previously separated lineages by forming highly diverse species complexes. We provide here the first molecular evidence of hybridization in wild populations of ciliates, a highly diverse group of free-living and symbiotic eukaryotic microbes. The impact of hybridization was studied on the model of Plagiotoma, an obligate endosymbiont of the digestive tube of earthworms, using split decomposition analyses and species networks, 2D modeling of the nuclear rRNA molecules and compensatory base change analyses as well as multidimensional morphometrics. Gene flow slowed down and eventually hampered the diversification of Lumbricus-dwelling plagiotomids, which collapsed into a single highly variable biological entity, the P. lumbrici complex. Disruption of the species boundaries was suggested also by the continuum of morphological variability in the phenotypic space. On the other hand, hybridization conspicuously increased diversity in the nuclear rDNA cistron and somewhat weakened the host structural specificity of the P. lumbrici complex, whose members colonize a variety of phylogenetically closely related anecic and epigeic earthworms. By contrast, another recorded species, P. aporrectodeae sp. n., showed no signs of introgression, no variability in the rDNA cistron, and very high host specificity. These contrasting eco-evolutionary patterns indicate that hybridization might decrease the alpha-diversity by dissolving species boundaries, weaken the structural host specificity by broadening ecological amplitudes, and increase the nuclear rDNA variability by overcoming concerted evolution within the P. lumbrici species complex.